Prevalence and Clinical Outcome of Hyperglycemia in the Perioperative Period in Noncardiac Surgery - Frisch, Anna (American Diabetes Association, 2010)
OBJECTIVE: Hospital hyperglycemia, in individuals with and without diabetes, has been identified as a marker of poor clinical outcome in cardiac surgery patients. However, the impact of perioperative hyperglycemia on clinical outcome in general and noncardiac surgery patients is not known. RESEARCH DESIGN AND METHODS: This was an observational study with the aim of determining the relationship between pre- and postsurgery blood glucose levels and hospital length of stay (LOS), complications, and mortality in 3,184 noncardiac surgery patients consecutively admitted to Emory University Hospital (Atlanta, GA) between 1 January 2007 and 30 June 2007. RESULTS: The overall 30-day mortality was 2.3%, with nonsurvivors having significantly higher blood glucose levels before and after surgery (both P < 0.01) than survivors. Perioperative hyperglycemia was associated with increased hospital and intensive care unit LOS (P < 0.001) as well as higher numbers of postoperative cases of pneumonia (P < 0.001), systemic blood infection (P < 0.001), urinary tract infection (P < 0.001), acute renal failure (P = 0.005), and acute myocardial infarction (P = 0.005). In multivariate analysis (adjusted for age, sex, race, and surgery severity), the risk of death increased in proportion to perioperative glucose levels; however, this association was significant only for patients without a history of diabetes (P = 0.008) compared with patients with known diabetes (P = 0.748). CONCLUSIONS: Perioperative hyperglycemia is associated with increased LOS, hospital complications, and mortality after noncardiac general surgery. Randomized controlled trials are needed to determine whether perioperative diabetes management improves clinical outcome in noncardiac surgery patients.